INNOVATIVE TECHNOLOGIES OF PEDAGOGICAL CONFLICTOLOGY STUDENTS TRAINING - Н. Кошечко (Київський національний університет імені Тараса Шевченка, 2018)
The article is devoted to the analysis of topical ideas on the problem of teaching students of high school pedagogical сonflictology. Specific emphasis is put on the technology of its study. The urgency of the problem lies in the fact that in today's Ukraine, pedagogical conflictology is gradually formed due to theoretical-empirical research. Scientists are actively developing historical, comparative, methodological, didactic and other aspects of it. From the beginning of the XXI century. pedagogical conflicts began to be studied in higher educational institutions due to the new discipline – pedagogical conflictology.Pedagogical conflictology – a field of scientific psychological and pedagogical knowledge about ways, ways and means of anticipation, prevention and overcoming of contradictions arising in the educational process of educational institutions. Knowledge of the essence, specificity and prevention of pedagogical conflicts in higher education can enhance the professional, intellectual and personal competence of students, teachers and heads of higher educational institutions. In the modern high school of Ukraine, it is desirable to prioritize not only traditional but also innovative educational technologies: coaching, mentoring, mediation, moderation and facilitation, which provide a high level of knowledge acquisition, acquisition of qualitative skills and abilities of students and have a perspective potential for the realization of the goals and objectives of the discipline. "Pedagogical Conflictology".After all, an important aspect of the professional training of students is not only the mastering of the relevant knowledge, but also the development of specific skills, which is possible in terms of practical training activities, which is a fundamental basis for the mastering of the discipline "Pedagogical Conflictology". In it the exclusive attention is directed to the development of students skills, skills of communicative activities, on its technology. In the field of education communicative, vocational and pedagogical competence becomes the main tool of the successful personality.

Здійснено аналіз актуальних ідей із проблеми навчання студентів педагогічній конфліктології. Особливий акцент поставлено на технологіях її вивчення. Виняткову увагу приділено коучингу, менторінгу, медіації, модерації, фасилітації.
ІННОВАЦІЙНІ ТЕХНОЛОГІЇ НАВЧАННЯ СТУДЕНТІВ З ПЕДАГОГІЧНОЇ КОНФЛІКТОЛОГІЇ
Keywords: педагогічна конфліктологія; технології навчання студентів; коучинг; менторинг; медіація; модерація; фасилітація; pedagogical conflictology; students' learning technology; coaching; mentoring; mediation; moderation; facilitation